2016
DOI: 10.1038/icb.2016.110
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic thrombomodulin promotes cell adhesion through interacting with its ligand, Lewisy

Abstract: The leukocyte adhesion cascade involves multiple events that efficiently localize circulating leukocytes into the injured sites to mediate inflammatory responses. From rolling to firm adhesion, the interactions between adhesion molecules have pivotal roles in increasing the avidity of leukocytes to endothelial cells. Thrombomodulin (TM), an essential anticoagulant protein in the vasculature, is also expressed on leukocytes. We previously demonstrated that Lewisy (Ley), a specific ligand of TM, is upregulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Many studies have suggested a role for Le y in inflammation, as it is expressed as a carbohydrate ligand for cell adhesion. 1,21,22 Thus, the expression of Le y on platelets may also contribute to adhesion and platelet aggregation. However, we found no correlation between the intrinsic Le y expression level and the aggregation rate in random Figure S1).…”
Section: The Possible Role Of the Le Y Antigen In Human Plateletsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have suggested a role for Le y in inflammation, as it is expressed as a carbohydrate ligand for cell adhesion. 1,21,22 Thus, the expression of Le y on platelets may also contribute to adhesion and platelet aggregation. However, we found no correlation between the intrinsic Le y expression level and the aggregation rate in random Figure S1).…”
Section: The Possible Role Of the Le Y Antigen In Human Plateletsmentioning
confidence: 99%
“…Wu et al demonstrated that leukocyte-expressed thrombomodulin (TM) is a ligand for Le y on the endothelium. 1 Thus, TM on the endothelium is also likely to be a ligand for platelet Le y . If so, this may also contribute to the adhesion of platelets to the endothelial matrix.…”
Section: The Possible Role Of the Le Y Antigen In Human Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of PKCδ with TM in the monocytic THP-1 cells leads to inhibition of the cell cycle and subsequent differentiation through ERK1/2 mediated cytoskeletal remodeling [67]. Moreover, monocytic TM is reported to bind Lewis-Y (LeY) on the inflamed endothelium, thereby triggering an increase in activation of p38 MAPK signaling [68]. This facilitates firm binding of THP-1 to ICAM-1 on the endothelium by activating β2 integrins on THP-1 cells [68].…”
Section: Thrombomodulin and Mapk Signaling In Leukocytesmentioning
confidence: 99%
“…Moreover, monocytic TM is reported to bind Lewis-Y (LeY) on the inflamed endothelium, thereby triggering an increase in activation of p38 MAPK signaling [68]. This facilitates firm binding of THP-1 to ICAM-1 on the endothelium by activating β2 integrins on THP-1 cells [68]. However, this process seems to operate under localized inflammatory conditions since systemic inflammatory molecules like LPS decreases the TM expression on THP-1 cells [69]…”
Section: Thrombomodulin and Mapk Signaling In Leukocytesmentioning
confidence: 99%